2018
DOI: 10.1103/physrevb.97.104512
|View full text |Cite
|
Sign up to set email alerts
|

Topology from triviality

Abstract: We show that bringing into proximity two topologically trivial systems can give rise to a topological phase. More specifically, we study a 1D metallic nanowire proximitized by a 2D superconducting substrate with a mixed s-wave and p-wave pairing, and we demonstrate both analytically and numerically that the phase diagram of such a setup can be richer than reported before. Thus, apart from the two "expected" well-known phases (i.e., where the substrate and the wire are both simultaneously trivial or topological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…[38] The transport properties of Weyl semimetal nanowires have been already studied by using the scattering matrix approach and numerical methods in refs. [39][40][41]. Remarkably, it was shown that the contribution of the Fermi arc states to the electric current induced by a slowly varying magnetic field can be significant and even comparable to that of the bulk states regardless of the system size.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[38] The transport properties of Weyl semimetal nanowires have been already studied by using the scattering matrix approach and numerical methods in refs. [39][40][41]. Remarkably, it was shown that the contribution of the Fermi arc states to the electric current induced by a slowly varying magnetic field can be significant and even comparable to that of the bulk states regardless of the system size.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was explicitly demonstrated [41] that the existence of the surface and bulk states allows for two transport regimes. In the surface regime, the current is carried by the Fermi arc surface states with conductance increasing in steps as a function of the electric chemical potential when it lies in the bulk confinement gap due to the finite size of a sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these adatoms order magnetically the chain can become a 1D topological superconductor, even if the underlying superconductor is of s-wave spin-singlet type. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The key point in this construction is that magnetic impurities in s-wave superconductors feature socalled Shiba midgap bound states, 18,21,[27][28][29][30] which can hybridize along the chain and experience band inversion. The appearance of Shiba states can be intuitively understood from "Anderson's theorem", 31 stating that s-wave superconductivity is (locally) suppressed by magnetic impurities.…”
Section: -11mentioning
confidence: 99%
“…The total Hamiltonian consists of the sum H = H (bulk) + H (imp) . Each potential impurity atom binds a single physical subgap state [42][43][44], which in the BdG formalism is represented by a pair of states at energies ε = ± where v F is the Fermi velocity and ν the density of states in the bulk [45].…”
mentioning
confidence: 99%